Games development: contribution to interactive infographics from a design perspective and methods. (Human Factors in Design, 2012)
The objective of this work is to look in the games production and development bibliography methods or steps that can be adapted to the design of digital interactive infographics production. As a projectual practice based in products development methodologies (physical and/or communicational) and information systems, design will be used in this work in order to aggregate the methods and steps found in a single methodological approach. Despite the interaction design is directly attached to both areas, it is the understanding that an open method without predefined sequential steps, serves better the proposal of unite these different areas of knowledge and create a greater integration between different professionals, needed to produce such pieces.